2016
DOI: 10.3390/f7040090
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Structure and Diversity of Woody Plants in a Secondary Mixed Pine-Oak Forest in the Sierra Madre del Sur of Mexico

Abstract: Abstract:The biotic province of the Sierra Madre del Sur presents a mosaic of woodlands at different successional stages due to frequent modifications in land use. In this study, we analyzed changes in woody flora across three successional stages of pine-oak forest: early, intermediate, and mature. Vegetation composition and diversity were characterized in 10 plots (each 0.28 ha). The mature stage had the highest values for species richness, abundance, and diversity. Pioneer plants were dominant in the early-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
2
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 57 publications
2
12
2
11
Order By: Relevance
“…In contrast, the remnants of these forests in 2015 are native areas that have remained unchanged since at least 1973, and the small proportion of this type of vegetation in a given successional stage contributes to an increase in species richness, since it has been observed that the presence of temperate plant communities with different succession times favors regeneration and allows for diversity [77]. Moreover, the spatial distribution of Temperate forests, both native areas and those with a successional process, was mostly concentrated in the northwestern part of the NPAAC, and agrees with the most recent categorization proposed in the official management plan for the study area [42], where the same region is recommended as an area for preservation and restoration of the oak-pine forest.…”
Section: Successional Stages Of the Main Types Of Vegetation In The Nmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the remnants of these forests in 2015 are native areas that have remained unchanged since at least 1973, and the small proportion of this type of vegetation in a given successional stage contributes to an increase in species richness, since it has been observed that the presence of temperate plant communities with different succession times favors regeneration and allows for diversity [77]. Moreover, the spatial distribution of Temperate forests, both native areas and those with a successional process, was mostly concentrated in the northwestern part of the NPAAC, and agrees with the most recent categorization proposed in the official management plan for the study area [42], where the same region is recommended as an area for preservation and restoration of the oak-pine forest.…”
Section: Successional Stages Of the Main Types Of Vegetation In The Nmentioning
confidence: 99%
“…In this regard, evidence shows that abandonment of cultivated areas and pasture fields results in the development of thorny vegetation [75], this being one of the communities considered within the Scrub vegetation in our study. In Mexico, it has been observed that early succession stages are characterized by a dominance of herbaceous and shrubs for both Tropical vegetation [76] and Temperate forests [77]. In addition, scrub vegetation exists as an ecotone with areas of these two vegetal communities [78].…”
Section: Successional Stages Of the Main Types Of Vegetation In The Nmentioning
confidence: 99%
“…With this data, we evaluated the foliage height diversity (FHD) using the Shannon-Wiener index. Detailed vegetation analyses for these sites are described in Almazán-Núñez et al [7].…”
Section: Vegetation Samplingmentioning
confidence: 99%
“…In temperate forest ecosystems of Mexico and other parts of the world, many anthropogenic activities (i.e., agriculture, overharvesting, and fires) have increasingly modified the composition and structural characteristics of vegetation [5,6]. As a consequence, many of these landscapes are currently characterized by secondary forest intermixed with scrublands, grasslands, and farmlands [7]. In these landscapes, vegetation in later successional stages is usually taller and has greater biomass, higher number of vertical structural components, and higher number of tree species [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation